2019
DOI: 10.15684/formath.001
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Analysis of Forest Stand Disturbances in Coastal Georgia (USA) Using Landsat Time Series Stacked Imagery

Abstract: A determination of forest characteristics across broad areas is of great concern to the forest industry in the southern United States, as timber supply decisions can be based on opportunities, or lack of thereof, across all wood procurement areas. This is important in areas such as the southern United States, where the land ownership distribution is highly fragmented and where no general comprehensive source of forest data exists other than the low-intensity USDA Forest Service FIA surveys. In an effort to des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Although the results of the accuracy assessment suggest that this new method is better than our previous analysis, which attempted to detect the disturbance history of seven counties in Coastal Georgia [20], our new method still contained several areas of concern. For instance, on the commission error side of the analysis, we found that some forest thinnings could have been misclassified as a final harvest disturbance.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Although the results of the accuracy assessment suggest that this new method is better than our previous analysis, which attempted to detect the disturbance history of seven counties in Coastal Georgia [20], our new method still contained several areas of concern. For instance, on the commission error side of the analysis, we found that some forest thinnings could have been misclassified as a final harvest disturbance.…”
Section: Discussionmentioning
confidence: 79%
“…However, as the GFC dataset provides the disturbance history starting only after the year 2000, it was necessary to develop our own model to detect the disturbances occurring from the 1980s onward. Although some research has been dedicated to partially tracking the forest disturbance history in Georgia [20][21][22], with the exception of the GFC, no research has covered the disturbance history of the entire state of Georgia.…”
Section: Introductionmentioning
confidence: 99%
“…The Piedmont ecoregion is located between the Appalachian Mountains and the Southeastern Plains, and it includes the Atlanta metropolitan area, where more than 50% of the Georgia population resides. In the Appalachian mountain area, most of the forests are hardwood or mixed forest that are less frequently disturbed [35].…”
Section: Study Areamentioning
confidence: 99%